The Effect Of Pedagogic Competences Toward Students’ Satisfaction - Hilda, Lelya (International Journal of Scientific Research and Management (IJSRM), 2018)
Nowadays, education must be able to compete with globalization. One of the importance factors is pedagogical competences that every student needs to have it to improve interesting and attractive as well as successful learning process. Based on the research result toward 200 students of Tarbiyah Faculty of IAIN Padangsidimpuan, it was found that students’ satisfaction is categorized as good in the mean of 76.75 and 77.53. The correlation 0.612 showed that there is a correlation and pedagocical competences affect only 37.4%. Then, the hypothesis proved that there is a significant effect of pedagogical competences toward students’ satisfaction with the result of anova Fh   =118.367 , sig 0.000 < 0.05, and the regression equation Ῡ = 0.561 x + 34.456.